STRATEGI PENINGKATAN DISIPLIN SISWA DI SEKOLAH - Uneh Dwiyanti; Lilis Kholisoh Nuryani; Sumiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Discipline is obeying the applicable regulations in one's environment, both formally and informally. Or carry out good attitudes in accordance with applicable rules and regulations. Carrying out a disciplined life needs to be trained and accustomed to in everyday life, because with this discipline all students at school will be truly trained and can feel a useful and serious life. They will gain trust from their peers, from teachers, from parents and the surrounding community. Because of their high sense of discipline and responsibility. The word discipline is something that is easy to say but difficult to do. The application of discipline both in Educational Units and in the community environment in everyday life must be optimized so that students/communities in carrying out learning well, are able to compete in the field healthily both at the District, Regency and Provincial levels and even to the national level. Therefore, in the development of discipline education, it is very necessary to have a strategy to improve student discipline in schools that is good and planned. This study is How is the strategy in improving student discipline at SMP Negeri 1 Kesugihan, Cilacap Regency. while the purpose of this study is to describe the strategy to improve student discipline at SMP Negeri 1 Kesugihan, Cilacap Regency. This research method uses descriptive qualitative research. The data sources in this study were obtained by researchers from key informants, namely people who can provide information to researchers, data collection techniques consisting of; Interviews, Observations, and Documentation. The findings of the research are the strategies used by SMP Negeri 1 Kesugihan, Cilacap Regency in improving student discipline, namely: a) Preparation of vision, mission, motto, and objectives, b) Preparation of special activity programs c) Rules of procedure, d) Socialization, e) Approach, f) Facilities and infrastructure, and g) Evaluation.